Coding and noncoding landscape of extracellular RNA released by human glioma stem cells. Issue 1 (December 2017) - Wei, Zhiyun; Batagov, Arsen; Schinelli, Sergio; Wang, Jintu; Wang, Yang; El Fatimy, Rachid; Rabinovsky, Rosalia; Balaj, Leonora; Chen, Clark; Hochberg, Fred; Carter, Bob; Breakefield, Xandra; et al.
Abstract Tumor-released RNA may mediate intercellular communication and serve as biomarkers. Here we develop a protocol enabling quantitative, minimally biased analysis of extracellular RNAs (exRNAs) associated with microvesicles, exosomes (collectively called EVs), and ribonucleoproteins (RNPs). The exRNA complexes isolated from patient-derived glioma stem-like cultures exhibit distinct compositions, with microvesicles most closely reflecting cellular transcriptome. exRNA is enriched in small ncRNAs, such as miRNAs in exosomes, and precisely processed tRNA and Y RNA fragments in EVs and exRNPs. EV-enclosed mRNAs are mostly fragmented, and UTRs enriched; nevertheless, some full-length mRNAs are present. Overall, there is less than one copy of non-rRNA per EV. Our results suggest that massive EV/exRNA uptake would be required to ensure functional impact of transferred RNA on brain recipient cells and predict the most impactful miRNAs in such conditions. This study also provides a catalog of diverse exRNAs useful for biomarker discovery and validates its feasibility on cerebrospinal fluid. While circulating DNA has been extensively explored as a potential cancer biomarker, RNA potential has been overlooked so far. Here the authors present a comprehensive analysis of extracellular RNA secreted by glioblastoma cells that could prove a valuable resource for biomarker discovery and a means of intercellular communication.